Revisión tecnológica de las patentes existentes de dispositivos para el monitoreo y control del efecto chatter en los procesos de fresado CNC (2022)
The metal-mechanical industry has had great evolution in the way of manufacturing parts, to the point of going from a manual modeling of parts to go through a modeling of parts by means of machinery, which in recent years have undergone significant changes for these machining processes, such as the integration of computer numerical control (CNC). The milling machine is one of these machines that uses computer numerical control (CNC), in which the machining process is not flawless, since there are circumstances beyond the control of the process, which are translated into a decrease in the quality of the parts. One of these factors is given in the vibrations created by the regenerative effect, since it is a periodic process of consecutive cuts, causing oscillations between the component and the cutting tool. In order to solve this problem, a technological evaluation is required to help researchers seeking to develop a method or device for the mitigation or reduction of the vibration effect in CNC milling machines and to be able to carry out the invention of their research based on the state of the art resolved in this project.